Robotic‐assisted surgery for rectal cancer with situs inversus totalis: A case report. Issue 4 (1st April 2021) - Kasai, Shunsuke; Hino, Hitoshi; Shiomi, Akio; Kagawa, Hiroyasu; Manabe, Shoichi; Yamaoka, Yusuke; Kato, Shunichiro; Hanaoka, Marie; Kinugasa, Yusuke
Abstract: We present a very rare case of rectal cancer in a patient with situs inversus totalis (SIT), which is a complete transposition of the thoracic and abdominal viscera. A woman in her 60s visited a local hospital reporting bloody stool and was diagnosed with upper rectal cancer and SIT. We made careful preoperative preparations for the congenital anomaly, and robotic‐assisted high anterior resection with D3 lymph node dissection was performed. Although we adopted an unusual six‐port placement, the operation was performed safely and efficiently without any adverse events. The patient recovered uneventfully. The pathological specimen was classified as pT3N2bM0 with negative resection margins. Robotic‐assisted surgery is advantageous for rectal cancer treatment even when anatomical abnormalities make the surgical procedure more difficult.